A case report of the treatment of diabetic foot ulcers using a sodium hyaluronate and iodine complex - Sobotka, Lubos; Smahelova, Alena; Pastorova, Jana; Kusalova, Marie (The international journal of lower extremity wounds, 2007)
Diabetic foot ulcers are difficult to heal due to defects in local microvasculature and persistent, concomitant infection. Despite the best medical care, amputation is often a management option for this problem. The authors have developed a new and unique system for wound treatment, which is based on a combination of high molecular weight sodium hyaluronate with an iodine complex-Hyiodine (Contipro C, Dolní Dobrouc, Czech Republic). In this case report, the authors present an observational study on a series of patients with diabetic foot disease with nonhealing wounds treated with Hyiodine. The effect of the HA-iodine complex was studied on 18 patients suffering from complicated foot diabetic wounds. The HA-iodine complex was either spread directly over the wound, or more frequently, gauze was immersed in the HA-iodine complex and then put on/into the wound. Then several layers of dry gauze covered the wound. This dressing was changed every 24 hours. Wound healing was monitored daily, and wound pictures were taken each second week. Clinical improvement was observed in the majority. This suggests that the HA-iodine complex dressing has potential that needs to be developed from controlled studies.
Keywords: senioři; gangréna; Wound Healing; Bandages; Diabetic Foot; Male; Middle Aged; jod; mužské pohlaví; Drug Combinations; hojení ran; fixní kombinace léků; Gangrene; kyselina hyaluronová; ženské pohlaví; Humans; Hyaluronic Acid; lidé středního věku; Iodine; adjuvancia imunologická; Adjuvants, Immunologic; obvazy; Aged; Female; lidé; diabetická noha